Pengembangan produk ecovault berbahan limbah kertas menggunakan pendekatan Design Thinking - Salma Aulia Husin; Sahiba Sahila; Rachmah Nanda Kartika; Fadillah Tri Widiawati; Florenthia Meylianthi; Kholifaturrahma; Erlangga Saputra (Universitas Atma Jaya Yogyakarta, 2026)
The increasing volume of cellulose-based waste has intensified the need to utilize paper waste into products with higher functional value. This material has considerable potential to be developed into functional products when processed through a systematic design approach. This study aims to develop Ecovault, an environmentally friendly storage product made from cardboard and paper pulp, using the Design Thinking approach. During the empathize stage, a survey was conducted to identify user needs, which indicated strong support for the use of recycled materials. The define stage identified two main issues: the low utilization of paper waste and the demand for small-sized storage products with an attractive appearance. The initial concept was realized in the form of a flower-pot-shaped storage through 3D rendering and subsequently tested through prototype development. The first prototype experienced structural issues, leading to a design revision by changing the pot shape from cylindrical to box-shaped. This modification improved the stability, strength, and structural neatness of the final prototype. The results demonstrate that paper waste can be transformed into functional and aesthetic storage products through an appropriate design approach.